Penerapan Model ARCS Untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu Di Sekolah Dasar - Firna Efriyenef; Yanti Fitria (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
This study aims to describe the application of the ARCS model to improve student learning outcomes in intergrated thematic learning in class IV UPTD SD N 01 IV Koto Talago, Lima Puluh Kota district. In this study, the type of classroom action research (CAR) was applied using qualitative and quantitative approaches. The subjects of this study were teachers and students of class IV, totaling 19 people. The results showed an increase in: a) RPP cycle I with an average of 82,9% (Enough) and cycle II with an average of 95,45% (Very Good), b) Imlement in the teacher activity of cycle I with an average of 81,25% (Enough) and cycle II with an average of 95% (Very Good), c) Imlement in the student activity of cycle I with an average of 81,25% (Enough) and cycle II with an average of 92,5% (Very Good). And student learning outcomes in the first cycle obtained an average of 74,75(Less) and in the second cycle 89,1 (Good). Based on these results, it can be concluded that the ARCS model can improve the learning process integrated thematic learning in grade IV elementary school.